(3GdCfjb aj GdeLGfjbs - (3GHf GQfHZG GdRQOcGTjs
(3ChdgG (B:s
(3GdMeO ddg eOHQ GdhLhO heDjO GdLfhO (B,(3HYO adeG cGf ef SeJ geJg GdYdjI gGeJG GdSeGc s
(3HgG CTcGd NGUI HBdGJ GdeLGfjb hcjajI GSJYeGdgG hGdgLhe HgGs
(3hHBNQgG ahGFO ddehGO GdcjeGFjI GdJi jJehf efgG GdHGQhOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B5 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CMeOGdKGdK (B/ (3GSJGfHhd (B(3469) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs